Tourists and Local Residents' Perceptions of Halal Tourism Efforts in Labuan Bajo - Eugenius Adisaputra Midy; Dudi Anandya (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Research on Local People's Perceptions of Halal Tourism Efforts in Labuan Bajo” Referring to this, practitioners and researchers recognize the importance of the tourism market (Battour and Ismail, 2016). Today the global Tourism Industry is becoming increasingly competitive. Understanding the needs, interests, demands, and behavior of international travelers is very important in destination development (Shafaei and Mohamed, 2015). The main research question of this research is "Research on Local Population Perceptions of Halal Tourism Efforts in Labuan Bajo" While the mini research question is as follows: What are the views of the community about efforts to implement halal tourism in Labuan Bajo?. This research is a basic research research, which is useful for increasing insight in social research related to the practice of building tourism potential through halal and non-halal tourism, especially in Labuan Bajo. Theoretically, qualitative research in practice is not singular, but diverse even though both are sheltered under the paradigm of interpretivism (Subadi, 2006:11). The qualitative data analysis technique is through three stages of coding or coding, namely Open Coding, Axial Coding, Selective Coding. The theoretical basis for Halal and Muslim-Friendly Tourism, Halal Awareness, Preception, Halal Tourism Characteristics and Attitude. In this study, the Government through the Tourism Office has a Halal tourism design that is misinterpreted by tourists and local communities. The concept of Halal tourism referred to by the government refers to additional friendly services for Muslim tourists who have different needs from other tourists such as worship facilities and halal food.